Tragedi di Balik Pembekapan: Ruptur Anterior Inferior Cerebellar Artery Sebagai Penyebab Kematian Mendadak Akibat Asfiksia - Liauw, Djai Yen; Sutanto, Eugenia Gerin; Natalie, Agatha Clarice; Anastasia Stella Carmelita; Leifon, Dave Edgar; Fungestu, Eyskens; Kaban, Felix Try Raka; Jusuf, Hans Jasper; Maria Victoria Isabella; Soedjianto, Susanna Gabriella; Tjiu, Wilsen (Jurnal Kedokteran Meditek, 2026)
Introduction: Mechanical asphyxia due to smothering is difficult to diagnose forensically because it often leaves no distinctive signs. Unlike strangulation or hanging, smothering using soft materials generally leaves no external traces, making the mechanism of death difficult to identify. Furthermore, epidemiological data on cerebral vascular rupture due to asphyxia are still limited. This case report aims to add to the forensic literature on variations in asphyxial deaths and strengthen the diagnosis of the cause of sudden death. Case Illustration: A 46-year-old woman was found in a supine position. External examination revealed bruising on the bridge of the nose, philtrum, lower lip, left shoulder blade, inner left upper arm, outer right thigh, and abrasions on the upper lip and left side of the neck caused by blunt force. Internal examination revealed two blood seepage sites in the neck muscles, an enlarged heart, dilated cerebral and cerebellar vessels, and haemorrhage in the posterior brainstem. Discussion: Autopsy findings indicated rupture of the anterior inferior cerebellar artery (AICA), suspected to be triggered by asphyxia. Asphyxia does not always cause death through direct hypoxia, but also through increased intracranial pressure that triggers cerebral blood vessel rupture. This mechanism can be caused by airway obstruction or cerebral venous occlusion. Conclusion: AICA rupture due to asphyxia is a rare phenomenon. Mechanical asphyxia due to smothering requires attention because it can cause hypoxia, decreased consciousness, and even death. This report serves as an important forensic reference in the diagnosis of sudden death due to asphyxia.